Diurnal Variation in Anaerobic Performance: Effect of Core Body Temperature - Mehmet Pense; Erbil Harbili; Sultan Harbili (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to investigate the effects of circadian rhythm on anaerobic performance and body temperature determined through three different methods. Ten elite male taekwondo athletes (average age: 23.9±2.7 years, height: 178.7±4.9 cm, body mass: 72.1±7.8 kg, training experience: 12.5±4.9 years) participated in the study. The body temperatures of the participants were measured in the morning of the first day, (between 09:00-10:00 a.m.), and in the early evening (between 16:00-17:00 p.m.) through three different methods (Core body temperature, tympanic temperature, and skin surface temperature). The participants performed Wingate test (WT) both in the morning and in the early evening. Core body temperature was significantly higher in early evening than it was in the morning (p lt;0.05), while tympanic and skin surface temperatures remained unchanged (p gt;0.05). However, there was no significant difference between morning and early evening for peak power, mean power, and fatigue index values (p gt;0.05). As a result, a significant increase was observed in core body temperature in early evening compared to morning, but this increase did not show a positive effect on anaerobic performance.